EDUKASI KOLABORASI UNTUK MENINGKATKAN PENGETAHUAN PASIEN STROKE TERHADAP TINDAKAN PERAWATAN DI RUMAH: Indonesia - Muhammad Ridha Afdhal Afdhal; Supriyati; Ismail Setyopranoto (Universitas Cokroaminoto Palopo, 2023)
Patient education is a part of a health promotion effort conducted by hospital to improve prevention and care for stroke patients. This study aimed to evaluate patient education services carried out by the Stroke Unit at Dr. Sardjito Hospital. Data collection was performed through in-depth interviews, observation, and document studies. Determination of participants was carried out by purposive sampling method in accordance with the specified inclusion and exclusion criteria. The number of participants in this study were 12 people. Participants consisted of 3 people (educational services), 5 people (education officers), and the target of education was the family of stroke patients (4 people). The validity of the data used triangulation method and triangulation sources. Education could increase the understanding and the awareness of patients and families of stroke patients in conducting disease diagnosis, prevention, treatment, and recovery from disease. The findings in this study were that collaborative education was not fully said to be more effective than independent education. Some educational targets found it difficult to understand the information provided in a comprehensive and massive manner. Some of the factors that influenced the target acceptance of education were education status, age, and the way the officer communicates the information. It was important to conduct an initial assessment upon the target characteristics before providing information in order the objectives of education implementation could be achieved optimally. The attitude and manner of delivering educators was also a key point for the success of education.